2019
DOI: 10.1016/j.jebo.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

The price effects of monetary shocks in a network economy

Abstract: Empirical evidence shows monetary shocks have two temporary effects on the distribution of prices. One, the dispersion of cross-section of prices increases in response to monetary shocks. Two, some prices change in the 'wrong' direction: some prices decrease in response to positive monetary shocks, and increase in response to negative monetary shocks. We present a model that generates the two effects of monetary shocks on the distribution of prices as an out-of-equilibrium phenomena. Firms are related to each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…Despite its use as a countercyclical tool to stimulate economic growth, monetary policy can also lead to an increase in prices due to an increase in money supply. This outcome is consistent with the findings of previous studies (Arintoko & Kadarwati, 2022;Nyumuah, 2018;Abbasinejad et al, 2018;Sethi et al, 2019;Mandel et al, 2019;Arintoko, 2021;Tai Nguyen et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite its use as a countercyclical tool to stimulate economic growth, monetary policy can also lead to an increase in prices due to an increase in money supply. This outcome is consistent with the findings of previous studies (Arintoko & Kadarwati, 2022;Nyumuah, 2018;Abbasinejad et al, 2018;Sethi et al, 2019;Mandel et al, 2019;Arintoko, 2021;Tai Nguyen et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…The relationship between economic growth and monetary policy, specifically the role of policy interest rates, was extensively examined by (Arintoko & Kadarwati, 2022) using the VAR method, which showed that policy interest rates respond positively to unexpected GDP changes. Previous studies have suggested that monetary policy plays a crucial role in regulating economic growth, inflation, and exchange rates (Nyumuah, 2018); (Abbasinejad et al, 2018); (Sethi et al, 2019); (Mandel et al, 2019) (Arintoko, 2021); (Tai Nguyen et al, 2022). (Kim & Lim, 2018) and (Kim et al, 2020) note that monetary policy shocks can affect exchange rates.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Various structural shocks that drive high inflation such as inflation shocks, output shocks, and exchange rate shocks are of greater concern to the central bank In many studies, monetary policy has an impact that includes the impact on output, inflation, and exchange rates. This empirical evidence is provided in studies conducted by, among others, Nyumuah (2018), Abbasinejad et al (2018), Sethi et al (2019), Mandel et al (2019), and Tai Nguyen et al (2022). The results of a study by Arintoko (2021) imply the important role of monetary policy in stabilizing output and inflation in the short run and stabilizing inflation in the long run.…”
Section: Introductionmentioning
confidence: 89%
“…Previous research has already shown that there is considerable dispersion in the response of sectoral prices to monetary shocks (see Balke and Wynne, 2007 ). In a production network model with capital requirement constraints, some firms will raise prices in response to a monetary tightening or lower prices after a monetary loosening, as shown by Mandel et al (2019) .…”
Section: Responses Of Prices To Monetary Policy Shocksmentioning
confidence: 96%